Islamic Guidance Patterns Through Habitual Religious Values in Shaping Children's Discipline Character - Kintan Aulia Batubara; Mailin Mailin (Scidacplus, 2026)
This study aimed to describe the discipline of early childhood children, the pattern of Islamic guidance through the habituation of religious values, and the obstacles and challenges encountered in fostering disciplined character among children at PAUD Satahi, Sipogu Village. The study employed a qualitative approach with a descriptive research design. The research informants consisted of one teacher and two parents of students, selected using a purposive sampling technique. Data were collected through observation, interviews, and documentation, and were analyzed using the Miles, Huberman, and Saldaña model, which includes data reduction, data display, and conclusion drawing. The findings revealed that the children's level of discipline had developed quite well, as indicated by their compliance with school rules, punctuality, responsibility in completing assigned tasks, and active participation in religious activities. The pattern of Islamic guidance was implemented through the habituation of praying before and after activities, greeting others with Islamic salutations, practicing politeness and good manners, participating in religious activities, teacher role modeling, providing advice, positive reinforcement, and fostering collaboration between the school and parents. The obstacles encountered included differences in children's characteristics and developmental levels, a lack of consistency in reinforcing religious habits within the family environment, the influence of the social environment and digital media, and limited time for character education at school. This study concludes that Islamic guidance through the habituation of religious values is an effective strategy for developing disciplined character in early childhood, as it integrates religious values, responsibility, and obedience to rules into children's daily lives.